The effectiveness of the picture exchange communication system (PECS) as an augmentative communication system for children with Autism Spectrum Disorders (ASD) : a South African pilot study - Travis, Julia (Division of Communication Sciences and Disorders, 2014)
Includes bibliographical references (leaves185-195).